Woodfordia fruticosa extract nanoemulsion: Influence of processing treatment on droplet size and its assessment for in vitro antimicrobial and anti-inflammatory activity - Najda, Agnieszka; Bains, Aarti; Klepacka, Joanna; Chawla, Prince (Frontiers in Nutrition, 2022)
Recently, plant-derived bioactive compounds have been utilized in the preparation of several functional food products; however, stability and water solubility are major constraints to these compounds. Therefore, to overcome this problem, the synthesis of nanoemulsion (oil in water) with varying concentrations of Woodfordia fruticosa flower extract (1%−10% w/v) was carried out and characterization of nanoemulsion was done. The average droplet size of nanoemulsion samples ranges from 149.25 to 244.33 nm. The control and WFNE3 nanoemulsion showed significantly (p < 0.05) higher thermal stability when correlated with average droplet size. An insignificant difference (p > 0.05) was observed in the average droplet size and zeta potential WFNE3 (−30.3mV) with the increased temperature rate. At varied pH ranges, WFNE3 showed significantly higher (p < 0.05) stability in comparison with the control nanoemulsion sample. In terms of ionic strength, WFNE3 nanoemulsion sample showed significantly (p < 0.05) higher stability, and with an increasing concentration of salt, the colloidal system of the WFNE3 sample showed significantly (p < 0.05) higher droplet size (318.91 nm). Therefore, the antimicrobial potential of WFNE3 nanoemulsion in comparison with extract of W. fruticosa flower extract was studied against Gram-positive Staphylococcus aureus, Gram-negative bacteria Pseudomonas aeruginosa, and fungal strain Candida albicans, respectively. WFNE3 nanoemulsion sample in comparison to flower extract showed a significantly higher (p < 0.05) zone of inhibition against gram-negative bacteria as compared to the control nanoemulsion sample upon storage for 7 days. WFNE3 nanoemulsion sample showed significant (p < 0.05) higher inhibition of protein denaturation (57.89%−87.65%) and (55.36%−83.58%) in comparison to control nanoemulsion sample (54.67%−80.28%) and flower extract (51.56%−79.36%), respectively. Due to these biological activities, the WFNE3 nanoemulsion sample could be scaled up to the industrial level for the formulation of varied types of functional foods.